2006
DOI: 10.1200/jco.2006.24.18_suppl.6528
|View full text |Cite
|
Sign up to set email alerts
|

Dasatanib (D) in patients (pts) with chronic myelogenous leukemia (CML) in lymphoid blast crisis (LB-CML) or Philadelphia-chromosome positive acute lymphoblastic leukemia (Ph+ALL) who are imatinib (IM)-resistant (IM-R) or intolerant (IM-I): The CA180015 ‘START-L’ study

Abstract: 6528 Background: Dasatinib (D) (BMS-354825) is a multi-targeted kinase inhibitor of BCR-ABL and SRC. Preliminary data from a phase I study suggest high efficacy of D in IM pretreated pts. Methods: START L is an open label phase II study of D in IM-R or IM-I pts with LB-CML and Ph+ALL conducted at 42 centers worldwide. D was given orally, 70 mg twice a day (bid), with escalation to 100 mg bid for poor response or reductions to 50 mg and 40 mg bid for toxicity. Pts had weekly blood counts and monthly bone marro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Phase II studies for dasatinib [32][33][34][35] in all phases of CML and Ph + ALL have been reported and supported rapid ap- proval of the compound (named Sprycel) on 6/29/06 for both indications; the recommended dose is 70 mg BID. In the "Start-C" trial of dasatinib in CP CML, 32 60% of patients required dose reductions over time for toxicity and the median dose was closer to 100 mg per day; ongoing trials continue to explore dosing options for dasatinib, including varying total dose and QD versus BID dosing.…”
Section: New Therapy To Address Imatinib-resistant Diseasementioning
confidence: 94%
“…Phase II studies for dasatinib [32][33][34][35] in all phases of CML and Ph + ALL have been reported and supported rapid ap- proval of the compound (named Sprycel) on 6/29/06 for both indications; the recommended dose is 70 mg BID. In the "Start-C" trial of dasatinib in CP CML, 32 60% of patients required dose reductions over time for toxicity and the median dose was closer to 100 mg per day; ongoing trials continue to explore dosing options for dasatinib, including varying total dose and QD versus BID dosing.…”
Section: New Therapy To Address Imatinib-resistant Diseasementioning
confidence: 94%
“…En modelos de línea celular, el dasatinib inhibió la mayoría de las mutaciones BCR-ABL referidas a la resistencia al imatinib, lo que puede explicar en parte la mayor eficacia reportada con el dasatinib in vitro. (26)(27)(28)(29) Una respuesta durable, tanto hematológica como citogenética y molecular ha sido demostrada con el dasatinib en estudios clínicos fase II y III, en pacientes con leucemia mieloide crónica (30)(31)(32).…”
Section: Introductionunclassified